Peran Organisasi Taruna Merah Putih dalam Membentuk Generasi Muda Berlandaskan Nilai-Nilai Pancasila sebagai Agen Perubahan di Provinsi Lampung - Nugraha Gading Priandana; Susan Febriyanti; Antonia Alda Resalda; Ana Mentari; Teki Prasetyo Sulaksono (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
This article reviews the contribution of the youth organization Taruna Merah Putih (TMP) in shaping the character of the young generation rooted in Pancasila values ​​in the Lampung Province. As a wing organization of the PDI Perjuangan, TMP focuses its activities on aspects of political education, leadership strengthening, and social activities to encourage the active role of youth in public and political spaces. By making Bung Karno's Trisakti the foundation of the movement namely political sovereignty, economic independence, and national personality TMP seeks to produce youth who have integrity and commitment to nationality. This study aims to analyze the strategic role of TMP in sowing Pancasila values ​​while empowering youth as agents of social transformation. The method used is descriptive qualitative with a literature study approach and participatory observation.